The authoring software tool in digital literature as a vector of the global imaginary. - Farge, Odile (Neohelicon, 2017)
Digital writing necessarily requires tools, software or technology. With its constant development, the technology must be 'intuitive' and easy to use, with no need for a manual. This intuitive use of the software authoring tool as a kind of universal language places it squarely in the globalization process. A question then arises: while allowing some degree of fair competition, does globalization not also entail a uniform way of producing, doing or thinking? Since the tools used by many digital authors were first developed for commercial purposes, we can ask whether this fact affects their imaginary when they write. Keeping in mind the globalized environment, I will illustrate the closed relationship in which the tools themselves make certain proposals and then anticipate certain specific practices, i.e., how globalization can structure the discourse and influence how authors think about creating their works. There is a globalized imaginary in which communications technology is becoming increasingly interconnected, and in which our imagination inevitably becomes globalized, reflecting beliefs and economic/socio-cultural structures that challenge national boundaries and shift the balance of power. Lev Manovich talks about 'cultural software' (2010), while Edgar Morin recognizes the existence of a global civilization that includes standard shared values. In this perspective, I will also examine the role of free software to see whether it can give rise to new communities and modify one production model of digital writing.